Platelet Analysis in Pediatric Patients with Acute Gastroenteritis at RSIA Sitti Khadijah 1 Makassar - Siti Muthiah Annisa Idris; Irna Diyana Kartika; Febie Irsandy Syahruddin; Irmayanti Haidir Bima; Andi Alamanda Irwan (Journal of Community Health Provision, 2026)
Acute gastroenteritis (AGE) is an inflammation of the stomach and intestines with symptoms of diarrhea, nausea and vomiting, experienced for less than 14 days, with a fairly high prevalence worldwide. One of the laboratory tests carried out is routine blood, including platelet count. When inflammation occurs, platelet production will increase in response from the immune system. To analyze platelets in acute gastroenteritis (AGE) sufferers. The methods of the research is descriptive retrospective using medical record data of acute gastroenteritis (AGE) sufferers. Results showed that the age distribution of samples was grouped into three groups, namely < 2 years, 3-5 years, and 6-10 years with the main complaints of diarrhea, vomiting, and diarrhea accompanied by vomiting. The platelet count of acute gastroenteritis (AGE) sufferers is more normal, but there is an increase in platelet count in the < 2 years age group with complaints of diarrhea accompanied by vomiting. There is no relationship between platelet count and complaints of diarrhea, vomiting, and diarrhea accompanied by vomiting in acute gastroenteritis (AGE) sufferers.